Clinical Effectiveness of Maintenance Electroconvulsive Therapy in Patients with Schizophrenia: A Retrospective Cohort Study. Issue 1 (March 2020) - Isserles, Moshe; Remington, Jesse; Kaster, Tyler S.; Daskalakis, Zafiris J.; Blumberger, Daniel M.
Abstract : Objective: This study aimed to assess the clinical effectiveness and cognitive effects of maintenance electroconvulsive therapy (mECT) in patients with schizophrenia or schizoaffective disorder and explore factors associated with both outcomes. Methods: In this retrospective cohort study, we examined clinical records of 47 patients with a Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition) diagnosis of schizophrenia or schizoaffective disorder treated with mECT at an academic mental health hospital between April 2010 and July 2016. Sixty-two mECT courses were reviewed. We assessed clinical effectiveness and cognitive effects as well as factors associated with response to treatment, including psychiatric diagnosis, concomitant pharmacological treatment, and previous treatment response. Results: Maintenance electroconvulsive therapy was able to maintain clinical response in 48 (77%) treatment courses. Significant cognitive adverse effects were reported in 7 (11%) of the courses. Use of antipsychotic, antidepressant or benzodiazepine medications, psychiatric disorder, and sex were not associated with response. Conclusion: This study shows meaningful clinical effectiveness and good tolerability of mECT in patients with resistant schizophrenia over extended periods.